1986
DOI: 10.1002/cjce.5450640119
|View full text |Cite
|
Sign up to set email alerts
|

Fischer‐tropsch synthesis in bubble column slurry reactors on FE/K‐catalyst

Abstract: Fischer-Tropsch synthcsis (FTS) on K promoted Fe catalyst was studied in three bubble column slurry reactors (BCSR) of 2.5. 5 , and 10 cm diameter. The objective was to check data reproducibility under conditions of arbitrary alterations of various parameters. First order rate constants evaluated on the basis of appropriate slurry reactor models were chosen as an approximate measure to characterize data reproducibility and catalyst activity. It was found that rate constants and hence reproducibility may differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
2

Year Published

1986
1986
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
1
7
0
2
Order By: Relevance
“…Several pilot plant slurry bubble columns have been constructed and operated in recent years (e.g. Deckwer et al, 1982;Kuo, 1983Kuo, , 1985Sanders et al, 1986). Although this type of reactor appears to be the most likely candidate for future commercialization of the slurry Fischer-Tropsch (F-T) process, it is not suitable for more fundamental studies due to its complex hydrodynamic behavior, which changes with the reactor size.…”
Section: ~~ ~mentioning
confidence: 99%
See 1 more Smart Citation
“…Several pilot plant slurry bubble columns have been constructed and operated in recent years (e.g. Deckwer et al, 1982;Kuo, 1983Kuo, , 1985Sanders et al, 1986). Although this type of reactor appears to be the most likely candidate for future commercialization of the slurry Fischer-Tropsch (F-T) process, it is not suitable for more fundamental studies due to its complex hydrodynamic behavior, which changes with the reactor size.…”
Section: ~~ ~mentioning
confidence: 99%
“…The stirred tank slurry reactor has been used for studies of the F-T synthesis by several investigators (e.g. Dyer et al, 1982a, b;Satterfield and Huff, 1982 a, b;Huff and Satterfield, 1984a, b;Stenger and Satterfield, 1985;Nettelhoff et al, 1985;Deckwer et al, 1986).…”
Section: ~~ ~mentioning
confidence: 99%
“…Our previous studies reported that impregnated Fe-K/Al 2 O 3 and co-precipitated Fe-Cu-Al-K catalysts gave a relatively high CO 2 conversion as well as high selectivity of olefins and long chain hydrocarbons in fixed bed reactors [11][12][13][14][15][16][17][18]. Recently, Fischer-Tropsch synthesis in fluidized bed or three-phase slurry reactors has been extensively investigated [19][20][21][22][23][24][25] because of its numerous advantages such as effective removal of heat generated from the exothermic reaction and high productivity of hydrocarbons due to effective contact among the reacting phases with higher heat and mass transfer rate and ease of continuous operation mode compared to the other contacting modes [24][25][26]. Thus, fluidized bed or slurry reactor can be expected to function as an effective system for the hydrogenation of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Statt dessen sollte jedoch eine Inhibierung durch CO, Beriicksichtigung finden. Um dies nachzuweisen, wurden in der von Sunders et al [3] beschriebenen MeRanlage mit einer Blasensaule von 10 cm Durchmesser Synthesegas-Umsatze an einem K-promotierten Fe-Fallungskatalysator gemessen. Dabei wurde bei einer hohen Katalysator-Konzentration (ca.…”
unclassified
“…Ordnung in H, ausgewertet, wobei unterschiedliche fluiddynamische Modelle unter Beriicksichtigung der Stofftransporthemmung an der Gas/Flussigkeits-Grenzflache angesetzt wurden. Dabei zeigte sich in Ubereinstimmung mit Sunders et al [3], daR das Vermischungsverhalten der Suspensionsphase (unvermischt, k', bzw. vollstandig vermischt, ky) fur die Ermittlung der Geschwindigkeitskonstanten k, 1.…”
unclassified